2013
DOI: 10.1111/his.12192
|View full text |Cite
|
Sign up to set email alerts
|

Mammary analogue secretory carcinoma of salivary glands is a lipid‐rich tumour, and adipophilin can be valuable in its identification

Abstract: MASC is a lipid-rich tumour containing large lipid droplets covered by adipophilin. This finding can be included among its defining immunohistochemical features, and possibly represents lactation-like secretory differentiation. Strong expression of STAT5a and cytoplasmic p63 in MASC reinforces this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
55
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 29 publications
12
55
0
5
Order By: Relevance
“…Furthermore, a recent study has shown that mammaglobin expression in MASC can be variable with complete lack of expression in a small subset [23]. This is further illustrated by the fact that one of our cases with rearranged ETV6 showed no mammaglobin expression.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…Furthermore, a recent study has shown that mammaglobin expression in MASC can be variable with complete lack of expression in a small subset [23]. This is further illustrated by the fact that one of our cases with rearranged ETV6 showed no mammaglobin expression.…”
supporting
confidence: 51%
“…Similarly, Carbonic anhydrase VI has recently been reported as an acinar marker and was shown to differentiate MASC from ACC with a sensitivity and specificity similar to DOG1 [38]. These findings suggest potential use of these markers as immunohistochemical tools [23]. Furthermore, two cases of non-NTRK gene fusion with ETV6 (ETV6-X fusion) have also been reported which appears to correlate with more aggressive histological features such as PNI and LVI [39].…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…These tumors were termed mammary analogue secretory carcinomas (MASC). Since this initial report, there have been approximately 100 additional cases published [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. These have been previously diagnosed as unusual variants of acinic cell carcinoma, adenoid cystic carcinoma, cystadenocarcinoma, mucoepidermoid carcinoma or adenocarcinoma, NOS.…”
Section: Mammary Analogue Secretory Carcinoma Of the Salivary Glandsmentioning
confidence: 99%
“…The proliferative rate ranges from 5 to 28 % [20]. Several recent studies demonstrated that the combination of S100, mammoglobin and especially large vacuole adipophilin staining is very helpful to eliminate almost all of the other differential diagnostic mimics of mammary analogue secretory carcinoma [24,27,30,39]. This latter stain is important, as occasionally mammoglobin, similar to acinic cell carcinoma, is only focally positive in MASC.…”
Section: Mammary Analogue Secretory Carcinoma Of the Salivary Glandsmentioning
confidence: 99%